Contrasting impact of androgens on male and female adiposity, fat distribution and insulin resistance in childhood and adolescence (EarlyBird 75). Issue 12 (2nd July 2020) - Chynoweth, Jade; Hosking, Joanne; Jeffery, Alison; Pinkney, Jonathan
Summary: Objectives: To investigate associations between androgens (testosterone, dehydroepiandrosterone sulphate [DHEAS] and androstenedione), adiposity, fat distribution and insulin resistance (IR) during childhood and adolescence. Methods: Three hundred and seven children (170 [55.4%] boys; 137 [44.6%] girls) recruited at age 5 and studied annually until age 16: androgens (liquid chromatography tandem‐mass spectrometry), anthropometry, body composition (dual‐energy x‐ray absorptiometry) and IR (homeostasis model assessment). Results: Early adiposity was associated with earlier detection of androstenedione in both sexes, and DHEAS in boys. At puberty, higher androgen levels were associated with favourable metabolic changes in boys, but adverse metabolic effects in girls. In boys, higher free testosterone (FT) was associated with lower body fat and android/gynoid fat ratio (AGR) (both P  < .001), but in girls higher total testosterone was associated with higher AGR. In girls only, higher androstenedione ( P = .02) and FT ( P = .01) was associated with higher IR during puberty. Conclusions: In pre‐pubertal children, adiposity is associated with higher secretion of androgen precursors. After pubertal onset, higher testosterone is associated with lower adiposity and AGR in boys, but higher AGR and IR in girls. Therefore, androgens have modest sex‐specific associations with children's total body fat, fat distribution and IR.